Health and social impacts of California wildfires and the deficiencies in current recovery resources: An exploratory qualitative study of systems-level issues. - Annie Rosenthal; Eric Stover; Rohini J Haar (PLoS ONE)
Background Wildfires in California have become more deadly and destructive in recent years, and four of the ten most destructive fires occurred in 2017 and 2018. Through interviews with service providers, this article explores how these recent wildfires have impacted surrounding communities and the role various recovery resources have played in responding to the short- and long-term health and social needs of survivors. Methods Using a purposive sampling methodology, we interviewed 21 health and social service personnel who assisted in wildfire recovery efforts in California in 2017 and 2018. The study participants worked or volunteered in medical facilities, social services agencies and philanthropy/nonprofit organizations located in communities affected by wildfires. Participants were asked about three common, overarching themes that fire-impacted communities navigate post-disaster: health issues, social issues, and response and recovery resources. Inductive coding was used to identify common subthemes. Results The two most frequently discussed social issues during interviews were housing and employment access. Mental and emotional well-being and access to health resources were identified as being the most challenging health concerns that survivors face post-disaster. Participants also identified the following private and public recovery resources that survivors use to attempt to restabilize following the fire: community support, county agencies, the Federal Emergency Management Agency (FEMA,) insurance companies and philanthropic organizations. However, participants noted that the cumulative impacts of these efforts still leave many of their patients and clients without the resources needed to restabilize emotionally, financially and physically. Finally, participants spoke about the community-wide, downstream impacts of wildfires, noting that "survivors" are not only those whose health is immediately compromised by the disaster. Conclusion Given the worsening wildfire seasons in California, we must increase our understanding of both the scope of the health and social issues that survivors navigate following a disaster, as well as the effectiveness and sustainability of recovery resources available to survivors. We must also understand the "ripple effect" that wildfires have on surrounding communalities, impacting housing access, social services, and health care access. More research and support, especially during the current COVID-19 pandemic, is urgently needed to improve our ability to support the health and social needs of wildfire survivors in the future.